Restricting shuttling in bis(imidazolium)…pillar[5]arene rotaxanes using metal coordination. Issue 1 (7th November 2018) - Langer, Philipp; Yang, Lixu; Pfeiffer, Constance R.; Lewis, William; Champness, Neil R.
Abstract : Metal coordination to a series of bis (imidazolium)-pillar[5]arene [2]rotaxanes through the formation of metal–carbene bonds facilitates a new strategy to restrict the shuttling motion in [2]rotaxanes. Abstract : Metal coordination to a series of bis (imidazolium)…pillar[5]arene [2]rotaxanes through the formation of metal–carbene bonds facilitates a new strategy to restrict the shuttling motion in [2]rotaxanes. Whereas the pillar[5]arene macrocycle rapidly shuttles along the full length of the bis (imidazolium) rod for the parent [2]rotaxane, Ag(i ) coordination to the imidazolium groups through the formation of N-heterocyclic carbenes leads to restricted motion, effectively confining the shuttling motion of the [2]rotaxane. The Ag(i ) coordinated [2]rotaxanes can be reacted further, either removing the Ag–carbene species to recreate the parent [2]rotaxane, or reaction with more bulky Pd(ii ) species to further restrict the shuttling motion through steric inhibition.